INTEGRASI FRAMEWORK LARAVEL DALAM PENGEMBANGAN PERANGKAT LUNAK SISTEM SMART PJU BERBASIS INTERNET OF THINGS - Jaelani, Maulana; Shandyasa, I Wayan; Care Khrisne, Duman (Jurnal SPEKTRUM; Vol 10 No 4 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i04.p27, 2023)
This study analyzes the use of Laravel structure in improving Internet of Thing IoT-based Smart Street Lighting software. This research applies the Software Development Life Cycle (SDLC) methodology approach with the waterfall method. The IoT Smart Street Lighting system is the focus in an effort to improve the efficiency of public street lighting. This methodology merger applies the Laravel structure in software development with structured steps. The vetting process begins with defining requirements, user interface (UI) plans, and data management. The execution stage involves applying Laravel for programming as per the framework's prerequisites. Thorough testing ensures functionality, security, and optimal execution. This approach enhances future development capabilities and program quality by combining Laravel technicalities and the waterfall approach, making the Intelligent Street Lighting System more responsive, robust, and efficient based on weather data.